Bomantara: Reinterpreting Batik Fabric Relief Surya Majapahit - Rizki Lestari (East Asian Journal of Multidisciplinary Research, 2022)
With the development of the times, all aspects are competing to create new, creative and innovative things, including batik motifs. Various kinds of batik motifs in the archipelago make batik a cultural heritage full of diversity. The main element that should not be left behind from batik is the motif because behind the motif is stored prayer, hope for the wearer, one of which is a batik cloth with the name Bomantara. "Bomantara: Batik Cloth Reinterpretation of Surya Majapahit Reliefs" is focused on styling the shape of motifs inspired by Surya Majapahit as the main motif. Supporting motifs draw the form of flora such as tendrils and flowers. Using the concept of reinterpretation as a concept of forming motifs that produces the novelty of motifs and adds to the diversity of batik motifs, especially the shape of Surya Majapahit. The purpose of creating batik cloth is 1) Explaining the concept used in the creation of batik cloth. 2) Visualization of the form of the work with the title Bomantara. 3) The embodiment of the work on the fabric as a whole.